Penerapan Teknik Spiral Fabric Sebagai Garnitur Evening Gown - Rohmat, Alya Azzahra; Nurindah, Mandhe Sekar; Sakti, Asri Wibawa (Corak, 2025)
The fashion industry is currently experiencing rapid growth, with design innovation being one of the key factors attracting consumer attention. One technique that has been widely applied is fabric manipulation. Although this technique is well-known in the fashion world, its application in evening gowns remains limited. The aim of this work is to explore the application of the spiral fabric technique as an embellishment in women's evening gown design. The research method used is the Three Stage Design Process, which includes the stages of problem definition and research, creative exploration, and implementation. In the problem definition stage, a review of market needs and consumer preferences is conducted, specifically targeting women aged 20 to 30, who are often in the phase of exploring their personal identity and style. The creative exploration stage results in a design concept incorporating the spiral fabric technique, inspired by the movement of the fins and tail of the Danio Slayer fish. The fabric exploration reveals that organza is the most suitable material to create a dynamic and clearly defined spiral effect. The implementation stage leads to the realization of a design that combines both aesthetic and functional elements. Further development recommendations include exploring other fabrics and applying this technique to broader fashion designs to create more innovative and original worksABSTRAKIndustri fashion saat ini mengalami perkembangan pesat, dengan inovasi desain sebagai salah satu faktor utama yang menarik perhatian konsumen. Salah satu teknik yang banyak diterapkan adalah fabric manipulation. Meskipun teknik ini telah dikenal dalam dunia fashion, penerapannya pada evening gown masih terbatas. Penciptaan karya ini bertujuan untuk mengeksplorasi penerapan teknik spiral fabric sebagai garnitur dalam desain evening gown wanita. Metode yang digunakan dalam penelitian ini adalah Three Stage Design Process, yang meliputi tahapan problem definition and research, creative exploration, dan implementation. Pada tahap problem definition, dilakukan tinjauan terhadap kebutuhan pasar dan preferensi konsumen, khususnya wanita berusia 20 hingga 30 tahun, yang sering berada dalam fase eksplorasi identitas diri dan gaya pribadi. Tahap creative exploration menghasilkan konsep desain dengan penerapan teknik spiral fabric yang terinspirasi dari gerakan sirip ekor ikan Danio Slayer. Hasil eksplorasi kain menunjukkan bahwa organza merupakan bahan yang paling tepat untuk menciptakan efek spiral yang dinamis dan terdefinisi dengan jelas. Tahap implementation kemudian mengarah pada realisasi desain yang memadukan elemen estetika dan fungsionalitas. Rekomendasi pengembangan lebih lanjut termasuk eksplorasi bahan lain dan penerapan teknik ini dalam desain busana yang lebih luas untuk menciptakan karya yang lebih inovatif dan orisinal.